Congenital fistula of the fourth branchial arch: Report of case with long‐lasting misdiagnosis. Issue 2 (1st January 2019) - Stadler, Thomas M.; Morand, Grégoire B.; Schmid, Stephan; Broglie, Martina A.
Key Clinical Message: Fourth branchial arch anomalies are extremely rare. The anatomic course of the fourth branchial arch fistula usually determines the delay in diagnosis. High clinical suspicion should be given to reoccurring neck infections in infants and young adults. Diagnosis is obtained by direct laryngoscopy. Abstract : Fourth branchial arch anomalies are extremely rare. The anatomic course of the fourth branchial arch fistula usually determines the delay in diagnosis. High clinical suspicion should be given to reoccurring neck infections in infants and young adults. Diagnosis is obtained by direct laryngoscopy.